Molecular dissection of mutations at the heterozygous thymidine kinase locus in mouse lymphoma cells. - Applegate, M L (1990)
The mouse lymphoma L5178Y TK+/- 3.7.2C cell line allows quantitation of induced TK(+/-)----TK-/- mutations at the heterozygous thymidine kinase (Tk) locus. TK-/- mutant colonies show a bimodal size distribution, reflecting a difference in the growth rates of the two size classes that is hypothesized to result from different degrees of genetic damage. The two homologous chromosomes 11 containing the alleles of the Tk gene in L5178Y 3.7.2C TK+/- cells are distinguishable at the cytogenetic level. We find, in addition, that the two alleles are distinguishable at the molecular level because of an Nco I restriction fragment length polymorphism at the 3' end of the gene. In a set of 51 large-colony and 48 small-colony TK-/- mutants induced by ionizing radiation or by chemical mutagens, we find that 78, including all except one of the small-colony mutants, have lost the Tk+ allele and that some of these have two to four copies of the remaining Tk- allele. Nineteen of the large-colony TK-/- mutants that do not show Tk+ allele loss show no other structural changes detectable at the level of Southern blot analysis. One shows a partial deletion. The variety of mutagenic lesions recorded at the heterozygous Tk locus may be representative of events observed in human malignancy and may include a wider range of mutagenic events than can be observed at hemizygous test loci.